Morphology, thermal and mechanical properties of biodegradable poly(butylene succinate)/poly(butylene adipate-co-terephthalate)/clay nanocomposites - Ibrahim, Nor Azowa; Chieng, Buong Woei; Wan Yunus, Wan Md. Zin (Taylor & Francis, 2010)
Sodium montmorillonite (Na-MMT) was successfully modified by octadecylamine (ODA) through a cation exchange technique that showed by the increased of basal spacing of clay by XRD. The addition of the organoclay into the PBS/PBAT blends produced intercalated-type nanocomposites with improvements in tensile modulus and strength. The highest tensile strength of nanocomposite was observed at 1 wt% of organoclay incorporated. A TGA study showed that the thermal stability of the blend increased after the addition of the organoclay by 1 wt%. SEM micrographs of the fracture surfaces show that the morphology of the blend becomes smoother with presence of organoclay.